2015
DOI: 10.1128/mbio.00114-15
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei RRM1 Is a Nuclear RNA-Binding Protein and Modulator of Chromatin Structure

Abstract: TbRRM1 of Trypanosoma brucei is a nucleoprotein that was previously identified in a search for splicing factors in T. brucei. We show that TbRRM1 associates with mRNAs and with the auxiliary splicing factor polypyrimidine tract-binding protein 2, but not with components of the core spliceosome. TbRRM1 also interacts with several retrotransposon hot spot (RHS) proteins and histones. RNA immunoprecipitation of a tagged form of TbRRM1 from procyclic (insect) form trypanosomes identified ca. 1,500 transcripts that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 71 publications
(95 reference statements)
1
45
0
Order By: Relevance
“…Five RBPs (Tb927.2.4710, Tb927.6.4440, Tb927.8.6650, Tb927.8.710, Tb927.11.350), which includes RBP42 previously shown to target mRNAs involved in energy metabolism (Das et al ., ), and two putative Zn‐finger proteins (Tb927.7.2670, Tb927.7.2680) were down‐regulated at the transcript level. Tb927.2.4710 may have an influence on transcription as it is a chromatin modulator (Naguleswaran et al ., ). However, at the protein level, and perhaps consistent with the contracted total RNA and mRNA content in metacyclics, fifteen RBPs and twelve Zn‐finger proteins were down‐regulated (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Five RBPs (Tb927.2.4710, Tb927.6.4440, Tb927.8.6650, Tb927.8.710, Tb927.11.350), which includes RBP42 previously shown to target mRNAs involved in energy metabolism (Das et al ., ), and two putative Zn‐finger proteins (Tb927.7.2670, Tb927.7.2680) were down‐regulated at the transcript level. Tb927.2.4710 may have an influence on transcription as it is a chromatin modulator (Naguleswaran et al ., ). However, at the protein level, and perhaps consistent with the contracted total RNA and mRNA content in metacyclics, fifteen RBPs and twelve Zn‐finger proteins were down‐regulated (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…D and (Naguleswaran et al. )). These results suggest that TbRRM1 might be involved in transcription repression of the SL‐RNA genes, as depletion of TbRRM1 increased their transcription.…”
Section: Resultsmentioning
confidence: 97%
“…Although it has been previously suggested that TbRRM1 does not play a role in global trans ‐splicing (Manger and Boothroyd ; Naguleswaran et al. ), it could be involved in the splicing processing of a small set of transcripts. We found that trans ‐splicing of both transcripts was unaffected (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations